The roles of small extracellular vesicles as prognostic biomarkers and treatment approaches in triple-negative breast cancer - Zhou, Yueyuan; Xiao, Zhongdang; Zhu, Wei (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) is a particularly aggressive and invasive breast cancer subtype and is associated with poor clinical outcomes. Treatment approaches for TNBC remain limited partly due to the lack of expression of well-known molecular targets. Small extracellular vesicles (sEVs) carrying a variety of bioactive contents play an important role in intercellular communications. The biomolecules including nucleic acids, proteins, metabolites can be transferred locally or systematically to recipient cells and regulate their biological states, and are involved in physiological and pathological processes. Recently, despite the extensive attraction on physiological functions of exosomes, few studies focus on the roles of sEVs in TNBC. In this review, we will summarize the involvement of sEVs in the tumor microenvironment of TNBC. Moreover, we will discuss the potential roles of sEVs as diagnostic markers and treatment therapy in this heterogeneous breast cancer subtype. We finally prospect the clinical application of sEVs in TNBC.